Flow cytometry diagnosis in myelodysplastic syndrome: Current practice in Latin America and comparison with other regions of the world. (April 2019) - Grille, S.; Iastrebner, M.; Lorand-Metze, I.; van der Velden, V.H.J.; Ikoma, M.R.V.; Vidal-Senmache, G.; Colado, E.; Rabelo-Carrasco, L.J.; Blanco, A.; Huamán-Garaicoa, F.; O'Connor, J.E.; Cao Pochintesta, C.; et al.
Highlights: This survey shows large practice heterogeneity in MDS diagnosis by FC among laboratories. The median number of markers used is high, yet there is low compliance with IMDSflow recommendations. Additionally there is scarce use of published flow cytometry scoring systems. Abstract: Background: Flow cytometry (FC) is a valuable tool for the diagnosis of myelodysplastic syndromes (MDS). We present results of a survey carried out to evaluate FC current practice for MDS diagnosis in Latin America (LA), focusing on markers used and characteristics of the clinical diagnostic report. Compliance to IMDSflow recommendations was also evaluated. These practices were then compared with those used in other countries. Methods: An online survey was sent through the Grupo Latino-Americano de Mielodisplasia to LA cytometrists and other international scientific societies. Results: 91 responses from 15 LA countries were received. The median of the number of markers used was 20 ± 4.5, but only 8.1% of participants adopted the complete panel proposed by the International/European LeukemiaNet Working Group (IMDSflow). We received 140 eligible answers from regions other than LA (66 Europe, 59 USA-Canada, 8 Oceania, 6 Asia and 1 Africa). LA utilized more markers for MDS diagnosis than USA/Canada (p = 0.006), but similar to Europe. The use of MDS scoring systems differed among regions: 10.3% in LA, 0% USA/Canada and 25.7% Europe reported the "Ogata score". Finally, 52.0% of all participants included a general interpretation statement in the final report about the consistency of the FC results with MDS diagnosis, with no statistical differences between regions. Conclusions: This survey shows a low compliance with the IMDSflow recommendations and a scarce use of the scoring systems proposed in the literature. However, the number of surface markers used is high. We will work to develop a FC consensus for MDS diagnosis adapted to the clinical practice requirements in LA.